2020
DOI: 10.15184/aqy.2019.99
|View full text |Cite
|
Sign up to set email alerts
|

The Keimoes 3 desert kite site, South Africa: an aerial lidar and micro-topographic exploration

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Such notions suppose a reliable understanding of the distribution of desert kites across space, which, as we shall explore in this paper, is actually lacking. Analogously, recent research has identified desert kites (or at least 'kite-like' structures), in several areas of Africa, such as Libya (Giannelli & Maestrucci, 2018), the Nile Valley (Storemyr, 2011), and South Africa (Lombard et al, 2020). These findings again emphasize the need to re-evaluate the current consensus regarding the spatial distribution of desert kites.…”
Section: Introductionmentioning
confidence: 67%
“…Such notions suppose a reliable understanding of the distribution of desert kites across space, which, as we shall explore in this paper, is actually lacking. Analogously, recent research has identified desert kites (or at least 'kite-like' structures), in several areas of Africa, such as Libya (Giannelli & Maestrucci, 2018), the Nile Valley (Storemyr, 2011), and South Africa (Lombard et al, 2020). These findings again emphasize the need to re-evaluate the current consensus regarding the spatial distribution of desert kites.…”
Section: Introductionmentioning
confidence: 67%
“…This analysis reveals the large portions of the country from which no recorded, radiocarbon dated human remains have been recovered. The result is probably an artefact of human remains collection practices, archaeological research focus, and preservation conditions on the one hand, and a broad reflection of population distribution and densities on the other (for the distribution of Stone Age vs Iron Age stone walling and occupation see Huffman 2007; Sadr 2012; Lombard et al 2020). Stone Age remains cluster around the coastal regions in the Western Cape and Eastern Cape, with some sites also located in the Northern Cape, KwaZulu-Natal, and Free State (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few years, the first kite-like structures from the southern hemisphere have been reported on the northern edge of the Nama Karoo Biome near Keimoes, in the Northern Cape Province of South Africa (Fig. 1a & c; van der Walt & Lombard 2018; Lombard et al 2020Lombard et al , 2021. These structures are described as low, stone-walled V-shaped funnels, at times covering several hundred square metres with long converging guiding arms that sometimes end in a round enclosure or 'head' (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, also possible that they were used for some forms of animal husbandry (e.g., Ingold 1986;Sommerseth 2011;Crassard et al 2015). Identifying who made them, and when, from a southern African perspective is challenging because their construction is more informal when compared with Iron Age, or farmer, stone walling further east in the higher rainfall zones (i.e., organised, stone-packed and coursed, e.g., Huffman 2007), and the general lack of associated surface archaeology, faunal and datable materials make it difficult to establish group identities and chronologies (Lombard et al 2020(Lombard et al , 2021. The Keimoes kites represent fixed features on the landscape in a region that has been occupied by both hunter-gatherer and herder groups over the last 2000 years (Orton & Parsons 2018).…”
Section: Introductionmentioning
confidence: 99%